THE ROLE OF MASS MEDIA IN SHAPING PUBLIC PERCEPTION OF ISLAMIC EDUCATION POLICY - Nasrudin, Anas; Firdaus, Dede Ridho; Herianto, Ii Puji; Jamalulel, Habib Alwi; Fauzi, Anis; Firdaos, Rijal (Jurnal Konseling Pendidikan Islam, 2025)
Islamic education plays a strategic role in shaping national civilization and character, particularly in Muslim-majority countries such as Indonesia, where it forms an integral part of the national education system. Beyond its function as a vehicle for knowledge transmission, Islamic education serves as a foundation for moral and ethical development rooted in Islamic values. In the era of globalization and rapid technological advancement, the adaptability of Islamic education becomes increasingly vital especially as mass media emerges as a powerful force in influencing public perception of related policies. This study explores how Islamic education policies are portrayed in the mass media, the extent to which such portrayals shape public opinion, and the patterns of framing and bias that may be present in media coverage. Employing a descriptive qualitative approach through literature review, the research draws on a range of sources including books, academic journals, news articles, and digital publications. The findings reveal that mass media significantly influence public attitudes toward Islamic education policy through agenda-setting and framing techniques. While mainstream media often align with government narratives, alternative media tend to highlight critical perspectives, including concerns about the potential secularization of Islamic education. The study concludes by emphasizing the need for more inclusive and transparent communication strategies involving collaboration among policymakers, scholars, and media practitioners to foster a more informed and balanced public discourse.